2017
DOI: 10.1007/s12282-017-0759-y
|View full text |Cite
|
Sign up to set email alerts
|

Social impacts of the work loss in cancer survivors

Abstract: In Japan, breast cancer was considered the leading cause for cost of work loss, and the most influential cause when the product of the "employment rate coefficient × productivity coefficient" for breast cancer was assumed the same as the product for all other types of cancers. It is necessary to establish support systems for working cancer survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…This study found that costs related to absenteeism, presenteeism, and indirect costs were significantly higher among caregivers (Table 6). A study in Japan examining the economic burden of cancer treatment on patients and their caregivers found that factors associated with work productivity loss among caregivers included treatment intensity, travel for treatment, and time spent on treatmentrelated activities necessitating altered working hours 39 . The need for informal caregivers in these situations that causes absence from work could be mitigated by initiatives for improved nursing care providing better support for patients during treatment administration, and innovative healthcare service offerings, for example, patient transport service to the site of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that costs related to absenteeism, presenteeism, and indirect costs were significantly higher among caregivers (Table 6). A study in Japan examining the economic burden of cancer treatment on patients and their caregivers found that factors associated with work productivity loss among caregivers included treatment intensity, travel for treatment, and time spent on treatmentrelated activities necessitating altered working hours 39 . The need for informal caregivers in these situations that causes absence from work could be mitigated by initiatives for improved nursing care providing better support for patients during treatment administration, and innovative healthcare service offerings, for example, patient transport service to the site of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, 41.0% of survivors took a leave of absence or quit their jobs. Cancer survivors' return to their jobs and household labor after the end of treatment is important to them and their families [6]. Di culty in returning to the role function they had before their cancer diagnosis negatively affects their QoL [42].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer survivors experience different physiological, psychological, functional, and social changes postrecovery [4][5][6]. When they adapt well to these changes, they are able to live a healthy life and improve their quality of life (QoL) [7].…”
Section: Introductionmentioning
confidence: 99%
“…For indirect cost incurred by the impairment of work productivity, higher annual indirect costs were associated with younger age and currently smoking. In Japan, Yamauchi et al 40 found breast cancer to be the leading cause of loss of work productivity in Japan because this frequently occurs during the most productive years of life, with half of breast cancer patients in Japan diagnosed while in their 30s to 50s. Our study also found a mere 14.2% of breast cancer patients were still in the labor force full time, and this was similar to females among colorectal and any types of cancer patients, indicating a need for support systems for working cancer survivors.…”
Section: Discussionmentioning
confidence: 99%